Influence of Reference Groups on Products Purchase Decisions of Young Adults: Examining the Impact of Peer Influence on the Purchase Decisions of Young Adults across Product Categories (Journal of Advances and Scholarly Researches in Allied Education, 2012)
There are some people that anindividual keeps in mind when making a purchase. Usually, such peopledisseminate opinions and other individuals are pressured into following theirtrend, becoming associated with them and using them as a standard of theirpurchase decisions. Such people are known as reference groups and they includeentertainment figures, sports heroes, political leaders, parents, co-workers,teachers and peers. This paper seeks to contribute to the existing body of theliterature on reference group influence. Specifically, it focuses on peerinfluence among young adults’ products purchase decisions.   A convenience sample of 101 universitystudents participated in this study. The results of Analysis of Variance andt-tests indicated that there is more normative influence for a public luxury(sunglasses) than for a private luxury (cell phone) and private necessity(toothpaste). Informational influence was also more for a public luxury than aprivate necessity.   Additionally, a publicnecessity (shoes) had more normative influence than a private luxury andprivate necessity as well as a high informational influence than privatenecessity. Overall, these results demonstrated that the influence of peersvaries across various product categories.